Emerging roles of SIRT1 activator, SRT2104, in disease treatment - Ning Chang; Junyang Li; Sufen Lin; Jinfeng Zhang; Weiqiang Zeng; Guoda Ma; Yajun Wang (Scientific Reports, 2024)
Abstract Silent information regulator 1 (SIRT1) is a NAD+-dependent class III deacetylase that plays important roles in the pathogenesis of numerous diseases, positioning it as a prime candidate for therapeutic intervention. Among its modulators, SRT2104 emerges as the most specific small molecule activator of SIRT1, currently advancing into the clinical translation phase. The primary objective of this review is to evaluate the emerging roles of SRT2104, and to explore its potential as a therapeutic agent in various diseases. In the present review, we systematically summarized the findings from an extensive array of literature sources including the progress of its application in disease treatment and its potential molecular mechanisms by reviewing the literature published in databases such as PubMed, Web of Science, and the World Health Organization International Clinical Trials Registry Platform. We focuses on the strides made in employing SRT2104 for disease treatment, elucidating its potential molecular underpinnings based on preclinical and clinical research data. The findings reveal that SRT2104, as a potent SIRT1 activator, holds considerable therapeutic potential, particularly in modulating metabolic and longevity-related pathways. This review establishes SRT2104 as a leading SIRT1 activator with significant therapeutic promise.